Electroactive properties of flexible piezoelectric composites - Sakamoto, Walter Katsumi [UNESP] (2001)
A flexible piezoelectric composite with 0-3 connectivity, made from Lead Zirconate Titanate (PZT) powder and vegetable-based polyurethane (PU), was doped with small amount of semiconductor powder. As a result a composite with 0-0-3 connectivity was obtained. The nature of absorption and steady state electrical conduction and the dielectric behaviour have been studied for this ceramic/polymer composite. The dielectric loss processes of the composite were observed to be dominated by those the polymer. Adding a semiconductor phase in the composite the electrical conductivity can be controlled and a continuous electric flux path could be created between the PZT grains. This composite may be poled at low voltage and in shorter time compared with composites without a conductive phase.